Application of rice husk as an adsorbent for the simultaneous removal of a multicomponent system of dyes: evaluation of the equilibrium and kinetics of the process (2018)
ABSTRACT: This work shows the adsorption study of a dye mixture onto rice husk (RH) by means of the firstorder derivative spectroscopy under a batch system, for which the anionic dye Red 40 (R40) and vat dye Indigo Blue (IB) were selected. This work shows for the first time the use of RH for the adsorption of a dye mixture formed by R40 and vat dye IB. The first-order derivative spectroscopy and analysis under a batch system were implemented. In order to establish the best conditions for the removal of these pollutants, a 23 full factorial design was initially carried out for each individual dye and then a 24 full factorial design for their mixture. Likewise, the equilibrium of the process was evaluated, taking into account the dyes as both mono-component systems and as part of the binary mixture, finding that Langmuir isotherm model is the one that offers the best fit for the experimental data of R40 (R2 = 0.987) and IB (R2 = 0.989), while competitive Langmuir model is the most suitable for the multicomponent system. As for the kinetics, the pseudo-second-order model shows the best fit for R40 (R2 = 0.970) and IB (R2 = 0.989), evaluated as individual dyes. This pseudo-second-order model also reproduces the experimental data of the mixture adequately. These findings point out that the adsorption of R40-IB dye mixture takes place through a competitive process, which is more favorable for the anionic dye R40. Furthermore, the achieved removal of 64.1% for this multicomponent system of dyes confirms that RH provides a potential adsorbent capacity and that this methodology is a viable approach for the treatment of colored effluents.